Analysis of Project Implementation Costs Using the Crashing Method in The Improvement of The Andongrejo-Bandialet Road, Jember District - Ardianto, Lukman; Wulandari, Esti; Witjaksana, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Construction project control is a systematic process aimed at ensuring that project objectives align with planning standards. One method used to accelerate project duration is "crashing," which involves reducing the time of specific activities that affect project completion, focusing particularly on activities on the critical path. This research adopts a descriptive method to collect and analyze data on the status of current symptoms related to project time management. Data collection was conducted through documentation, utilizing records, images, and work outputs. The results show that total project costs decrease significantly as the level of time compression (reduction of project duration) increases. However, increasing labor costs exhibits a small but consistent rise, indicating lower cost efficiency. The most optimal project costs were observed when additional working time was utilized, as opposed to adding more labor. In conclusion, while the crashing method is effective for reducing the risk of fines and indirect costs, selecting the best alternative requires balancing productivity and marginal costs (cost-time trade-off). For similar projects, extending working hours proves more cost-effective than increasing workforce size.